Using Charpit's method
we have the following equation,
"\\frac{dp}{\u2212pqy+2pz}=\\frac{dq}{\u2212pqx+2qz}=\\frac{dz}{2pqxy}=\\frac{dx}{qxy}=\\frac{dy}{pxy}"
using multipliers p ,q, x & y in 1st, 2nd, 4th & 5th equations and equating it with equation 3rd.
"\\frac{dz}{2pqxy}=\\frac{(pdx+qdy+xdp+ydq)}{pqxy+pqxy\u2212pqxy+2pxz\u2212pqxy+2qyz}"
from equation
"z^3=pqxy"
"\\frac{dz}{2z^3}=\\frac{(pdx+qdy+xdp+ydq)}{2pxz+2qyz}"
"\\frac{dz}{2z^3}=\\frac{(d(px)+d(qy)}{2pxz+2qyz}"
"\\frac{dz}{z^2}=\\frac{d(px)+d(qy)}{px+qy}"
Integrate both the sides and we get
"-\\frac{1}{z}=log(px+qy)+logc"
"\\frac{1}{z}=-log((px+qy)c)"
Comments
Leave a comment